Position of the hioid bone in relation to the volume of the airway in the different skeletal patterns - Ramos Vergaray, Mariela (2018)
Objective: Determine the position of the hyoid bone in relation to the volume of the airway oropharynx in the different skeletal patterns using cone beam volumetric tomography. Materials and methods: Thirty-nine tomographic volumes of patients who met the inclusion criteria of the Radiology Service of the Dental Center of the University of San Martín de Porres from 2014 to 2017, the skeletal class was determined by the angle ANB, the analysis of the volume of the airway oropharynx was carried out performed with the tools of the software explorer Romexis 4.4 (Helsinki, Finland) and the antero-posterior position of the hyoid bone, was determined by the measurement of the C3-H plane. Once the numerical values were obtained, the Pearson correlation test was applied. Results: the correlation between the volume of the airway oropharynx and the position of the hyoid bone in class I patients is 0.651, class II 0.173 and class III 0.187 which indicates that there is no correlation. However, in the determination of the volume of the airway in the different skeletal patterns, marked differences were found between each group. Conclusions: there is not enough evidence to state that there is a statistically significant correlation between the anteroposterior position of the hyoid bone and the volume of the airway oropharynx in the different skeletal patterns .